DAMPAK PERUBAHAN BUDAYA DAERAH LOWU-LOWU TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; Bela Man’ Nuri Gaiful (CV. ADIBA AISHA AMIRA, 2026)
Cultural changes in society also influence education, especially in elementary schools. Lowu-Lowu as a coastal area experiences socio-cultural transformation due to globalization, technology development, and lifestyle changes. This study aims to describe the impact of cultural change in Lowu-Lowu on learning processes in elementary schools. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that cultural changes affect students’ attitudes, motivation, and interaction patterns in learning. On one hand, cultural change brings positive impacts such as increased technological literacy, but on the other hand it causes challenges such as decreasing interest in local culture and learning discipline. Therefore, schools need to integrate local cultural values into learning to maintain students’ identity.